Rhodium and Iridium Amino, Amido, and Aminyl Radical Complexes - Donati, N; Stein, D; Buettner, T; Schoenberg, H; Harmer, J; Anadaram, S; Gruetzmacher, H (2008)
The chlorido-bridged dimeric complex [Rh2(μ-Cl) 2(trop2-NH)2] [trop2NH = bis(benzo[a,d]cycloheptenyl)amine] or the acetonitrile complexes [Rh(trop 2NH)(MeCN)2]+ (CF3SO 3-) and [IrCl(MeCN)(trop2NH)] are well-suited precursor complexes for phenanthroline-type complexes [M(trop 2NH)(R,Rphen)]+A- (M = Rh, Ir; R = H, Me, Ph substituents in the 4,7- or 5,6-positions of the phen ligand, A- = CF3SO3-, PF6-). These complexes contain 18-valence-electron configured metal centers in a trigonal-bipyramidal coordination sphere with the amino (NH) group in an axial position and each of the olefinic C=Ctrop units is in an equatorial position. The cationic amino complexes [M(trop2NH)(R,R-phen)] + are sufficiently acidic (pKa in dmso: 18.2-19.0) to be quantitatively deprotonated by one equivalent of KOtBu to give neutral amido complexes [M(trop2N)(R,R-phen)] (M = Rh, Ir). These can be easily oxidized to give aminyl radical complexes [M(trop2N .)(R,R-phen)]+A-, which for M = Rh can be isolated as green crystals. The iridium complex [Ir(trop2N .)(phen)]+ is unstable. High-resolution pulse EPR spectroscopy was used to gain insight into the electronic structure of the aminyl radical complexes. Remarkably, the rhodium and iridium complexes have a very similar electronic structure, as revealed by their EPR parameters {[Rh(trop2N.)(phen)]+: g1,2,3 = 2.084(2), 2.049(2), 2.027(2); |Aiso| = 45.4 (N1), 10.4 (N2), 3.1 (N3) 27.0 (Rh) MHz; [Ir(trop2N.)(phen)]+: g 1,2,3 = 2.140(2), 2.107(2), 2.015(2); |Aiso| = 47 (N1), 7.9 (N2), 3.5 (N3), 26.8 (Ir) MHz} and these show that about 60% of the spin population is localized on the nitrogen center (N1) of the trop2N ligand. In reactions with stannanes (R3SnH) and thiols (RSH), H-atom transfer to the trop2N nitrogen atom is observed, [M(trop 2N.)(phen)]+ + EH → [M(trop 2NH)(phen)]+ + 1/2HE-EH. © Wiley-VCH Verlag GmbH and Co. KGaA, 2008.